EFFECT OF ACOUSTIC MATERIAL CEILING TO SPEECH PERFORMANCE OF CONVENTION HALL - Muhammad Saladin Prawirasasra (Universitas Sebelas Maret Surakarta, 2018)
During design process of auditorium, mostly, acoustics design was neglected by engineers therefore it may cause inappropriate acoustic condition. Evaluation of acoustic comfort was carried out through measurement of speech parameters such as Noise rating (NR), reverberation time and definition (D50). According to measurement result, performance of convention hall is not sufficient to perform speech activities since it has 0.4-13.7 s of reverberation time and 1.6-42.6% of D50. To improve acoustic performance, modification is applied on ceiling materials using combination of two different acoustic materials – absorber and diffusor, through simulation.. The result has shown that installment of full absorber at ceiling with high absorbtive coefficient could reduce early energy reflection which causes lower reverberation time and higher definition. Whenever ceiling are made of combination of two type of materials, the position of di on ceiling depend on diffusor orientation. Spread diffusor has better performance rather than centralized diffusor. However, the acoustic performance of convention hall remains the same.